Influences of friction stir processing parameters on microstructure and mechanical properties of SiC/Al composites fabricated by multi-pin tool. (February 2019) - Tang, Jingming; Shen, Yifu; Li, Junping
Graphical abstract: Highlights: The newly designed multi-pin tool was employed to fabricate the AMCs reinforced by SiC particles by FSP. The reasonable matching of FSP process parameters was explored. A model for the influence of pin on the flow of plastic materials was established. The influences of the size and distribution of SiC particles on the microstructure properties of the AMCs were discussed. Abstract: The process parameters are the key factors that affect the microstructure and properties of aluminum matrix composites (AMCs) fabricated by friction stir processing (FSP). In the present investigation, the traditional single-pin tool and the newly designed multi-pin tool were employed to fabricate the AMCs reinforced by the SiC particles by FSP under different process parameters. The influences of process parameters on the microstructure, microhardness and wear behaviors of the composites were investigated. The reasonable matching of FSP process parameters was explored. A model for the influence of pin on the flow of plastic materials was established. The size of the SiC particles was minimized and uniformly distributed in the FSPed AMCs when the multi-pin tool at 950 rpm rotational speed and 40 mm/min traverse speed. The effect of stir and friction on the material was enhanced by the multi-pin tool compared to the single-pin tool, and increased the offset and broadening of the diffraction peaks of Al and SiC in the FSPed AMCs. The FSPed AMCs fabricated with the multi-pin tool had higher and less fluctuation microhardness than that with the single-pin tool under the same process parameters, as well as lower friction coefficient and less wear mass loss. The wear mechanisms of the FSPed AMCs changed from abrasive wear to adhesive wear as the size of SiC particles decreased.